The association between consanguineous marriage and offspring with congenital hearing loss - Almazroua, Aljohara M. (Ann Saudi Med, 2020)
BACKGROUND: Consanguinity is a commonly recognized practice among marriages in the Middle East and may lead to an increase in the prevalence of inherited disorders. Autosomal recessive deafness is the most common form of inherited congenital hearing loss (CHL). OBJECTIVES: Determine the association of consanguineous marriages with congenital sensorineural hearing loss (SNHL) and auditory neuropathy. DESIGN: Descriptive and analytical cross-sectional study. SETTING: Ear specialist hospital. PATIENTS AND METHODS: Children with severe-to-profound congenital SNHL, who had been referred to the specialist hospital for cochlear implant were analyzed. Patients were divided into subgroups based on degree of consanguinity. MAIN OUTCOME MEASURE: The relative risk of having more than one child with SNHL in offspring of a consanguineous marriage. SAMPLE SIZE: 189 parents and children with CHL. RESULTS: The parents of 157 children (83.1%) were blood-related. Of those, 48 had more than one child with CHL (31.4%), while only two parents who were not blood-related had more than one child with CHL (6.25%; P=.005). Among the 189 children, 131 (69.3%) parents were direct cousins. Only 39 (20.6%) and 43 (22.8%) children had family histories of CHL on the paternal and maternal sides, respectively. There was no statistically significant difference in the prevalence of auditory neuropathy between the offspring of consanguineous and non-consanguineous marriages (P=.648). CONCLUSION: The risk of having more than one child with SNHL in the offspring from a consanguineous marriage is 3.5 times higher than that of a non-consanguineous mating. LIMITATION: The association of hearing loss degree with consanguinity was not studied. CONFLICT OF INTEREST: None.